Underground Petersburg : Radical Populism, Urban Space, and the Tactics of Subversion in Reform-Era Russia - Ely, Christopher David, 1963- (Book collections on Project MUSE., 2016)
Although the radical populist movement that arose in Russia during the reign of Tsar Alexander II has been well documented, this important study opens with questions that haven't yet been addressed: How did Russian radical populists manage to carry out a three-year campaign of revolutionary violence, killing or wounding scores of people, including top government officials, and eventually taking the life of the tsar himself? And how did this all occur under the noses of the tsar's political police, who deployed vast resources and huge numbers of officials in an exhaustive effort to stop the killing? In Underground Petersburg, Christopher Ely argues that the most powerful weapon of populist terrorism was the revolutionary underground it created. Attempts to convey populist ideals in the public sphere met with resistance at every turn. When methods such as propaganda campaigns and street demonstrations failed, populists created a sophisticated urban underground. Linked to the newly discovered weapon of terrorist violence, this base of operations allowed them to live undetected in the midst of the city, produce their own weaponry, and attempt to ignite an insurrection through violent attacks putting terrorism on the map as a technique of political rebellion. Accessible to non-specialists, this insightful study reinterprets radical populism, clarifying its crucial place in Russian history and elucidating its contribution to the history of terrorism. Underground Petersburg will appeal to scholars and students of Russia, as well as those interested in terrorism and insurrectionary movements, urban studies, and the sociology of subcultures.